The Impact of Motivation and Commitment on Gen Z Work Performance in the Jabodetabek Area - Trisandri, Muhammad Iqbal Revilliano; Iskandar, Yusuf (Poltanesa, 2024)
This study explores the impact of motivation and commitment on the work performance of Gen Z (Generation Z) employees in the Jabodetabek area. The study aims to identify the most significant factors influencing the work performance of Gen Z in the Jabodetabek area, a demographic group known for their technological fluency and career development aspirations, and focus on work-life balance. The research employs a quantitative approach. The findings contribute to understanding how motivation and commitment can be leveraged to improve work performance in the Jabodetabek region, a critical hub for businesses and organizations in Indonesia. The study's results provide valuable insights for managers and policymakers seeking to optimize the performance of their workforce, particularly in the context of the evolving work dynamics driven by digitalization and the changing preferences of younger generations. This research helps to see the development of employee performance, especially in Gen Z, a generation that has just entered the world of work. The results showed that work motivation contains a positive and critical impact on the performance of Gen Z workers, work commitment encompasses a positive and noteworthy impact on the performance of Gen Z workers, also simultaneously work motivation and work commitment have a positive and noteworthy impact on the performance of Gen Z workers in Jabodetabek area